DEVELOPING THE SPIRIT OF INTERCULTURAL COMMUNICATION - Umar - Farouk (Politeknik Negeri Semarang, 2015)
Recently the news about radicalism,terrorism, social conflict et cetera haveappeared in many printed and elcetronicmedia. In spite of the spirit to improve thequality of human communication in the globalera, this fact makes most people worried ofthe future of international or interculturalcommunication. Briefly this article discussesethnocentrism, stereotype, world view, beliefsystem, normative values, and attitude as thefactors which can be the constraints indeveloping intercultural communication.Some historical overview relating to the issueof intercultural communication is alsohighlighted.